Method for detecting content of rare earth elements in tungsten material
Patent Information
- Application Number
- CN202310902885.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-07-21
AI Technical Summary
[0006]为解决上述现有技术中检测效率低,准确度不足及检测范围小的问题,本发明提供一种钨、钼材料中稀土元素含量检测方法,步骤如下:
[0018]基于上述,与现有技术相比,本发明提供的钨、钼材料中稀土元素含量检测方法,采用双氧水溶解样品,无需除钨基体,避免了其他溶解方法去除钨基体带来的共沉效应,提高了测定准确度,能很好的满足钨、钼合金中稀土元素的测定要求。同时测定范围广,能适应质量分数范围在0.01%~10%内,尤其是0.1%~10%范围内的稀土元素的检测需求,具有良好的应用价值。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal element detection technology, and in particular to a method for detecting the content of rare earth elements in tungsten materials. Background Technology
[0002] Rare earth elements are added to tungsten and molybdenum materials to improve their performance, and the detection of rare earth element content is crucial for the quality control of these materials. Existing methods for detecting rare earth elements in tungsten and molybdenum materials include: Chemical methods: In the detection of rare earth elements, the main focus is on lanthanum, yttrium, and cerium. Cerium requires the formation of cerium hydroxide precipitate with ammonia, followed by separation from tungsten and determination using ferrous ammonium sulfate titration. Lanthanum and yttrium require precipitation in an alkaline medium using magnesium as a carrier, followed by colorimetric determination. Because the chemical method requires precipitating the tungsten matrix and then separating lanthanum through filter paper and a funnel, the testing efficiency is extremely slow. Furthermore, losses during filtration also affect the accuracy of the results.
[0003] Spectroscopic methods: Inductively coupled plasma atomic emission spectrometry (ICP) is mainly used to determine rare earth elements. The sample preparation process involves adding hydrofluoric acid and nitric acid, followed by washing with perchloric acid to remove tungsten as tungstic acid. The resulting sample is then tested. The overall process is cumbersome, and the strong acid causes significant corrosion to the testing equipment. Furthermore, if the spectroscopic testing equipment uses a hydrofluoric acid-resistant system, its precision and accuracy are significantly affected.
[0004] Meanwhile, in the field of metal element detection, "major" usually refers to the range of 1% or more, "trace" usually refers to the range of 0.01% to 1%, and "ultra" usually refers to the range of less than 0.01%. However, the current three detection methods are only applicable to the trace range; when the rare earth element content exceeds the trace range, accuracy will decrease.
[0005] Therefore, how to ensure the accuracy and range of detection while improving detection efficiency has become a major hot topic in the field of tungsten and molybdenum material testing. Summary of the Invention
[0006] To address the problems of low detection efficiency, insufficient accuracy, and small detection range in the existing technologies, this invention provides a method for detecting rare earth element content in tungsten and molybdenum materials, comprising the following steps: The rare earth-doped alloy sample to be tested was pre-treated by crushing to obtain sample powder. The sample powder is dissolved in a dissolving solution to obtain the sample solution to be tested; Standard curves for tungsten and molybdenum alloys were established, and inductively coupled plasma mass spectrometry was used to detect the sample solutions. The dissolving solution includes at least hydrogen peroxide; The matrix of the rare earth doped alloy sample is any one or a combination of tungsten and molybdenum.
[0007] Specifically, the hydrogen peroxide is preferably hydrogen peroxide with a mass fraction of 30%.
[0008] In one embodiment, the pulverization pretreatment process is as follows: After cleaning the surface of the sample to be tested with a cleaning solution, it is washed with water, dried, and then crushed into powder particles to obtain the sample powder.
[0009] Specifically, the cleaning solution is hydrochloric acid or an alkaline solution.
[0010] In one embodiment, the powder particles have a particle size of at least 300 mesh.
[0011] In one embodiment, the dissolution process is as follows: Place the required weight of the sample powder into a reaction vessel, add hydrogen peroxide, and after the sample powder dissolves and becomes clear, bring the volume to a final volume to obtain the sample solution to be tested.
[0012] Specifically, when the sample powder is a tungsten alloy material, 0.1g is weighed; when the sample powder is a molybdenum alloy material, 0.25g is weighed.
[0013] In one embodiment, when the rare earth-doped alloy sample is doped with cerium, sulfuric acid is added after hydrogen peroxide is added and dissolved until cerium oxide precipitate appears at the bottom. Specifically, sulfuric acid with a volume fraction of 50% can be used.
[0014] In one embodiment, the rare earth element doping content in the rare earth-doped alloy sample is 0.01% to 10% by mass fraction. Preferably, the rare earth element doping content in the rare earth-doped alloy sample is 0.1% to 10%.
[0015] In one embodiment, the rare earth element in the rare earth doped alloy sample is any one or a combination of lanthanum, cerium, praseodymium, samarium, gadolinium, neodymium, gadolinium, erbium, ytterbium, lutetium, and yttrium; preferably any one or a combination of lanthanum, cerium, praseodymium, samarium, gadolinium, neodymium, and yttrium.
[0016] In one embodiment, the standard curve establishment process is as follows: Five 0.1g pure tungsten samples or 0.25g pure molybdenum samples were weighed, dissolved in hydrogen peroxide, and then 0, 0.5, 1, 2, and 4 mL of 1000ppm target rare earth element standard solution were added respectively. The volume was then adjusted to 100 mL. The solutions of each concentration were then placed in an inductively coupled plasma mass spectrometer. The instrument displayed the intensity values of the target rare earth element at each concentration point and fitted the intensity values with the corresponding concentration values to form a curve.
[0017] In one embodiment, the inductively coupled plasma mass spectrometry detection method is as follows: Select the wavelength of the element to be measured; set the concentration of the standard curve of the element to be measured; conduct the test at a test power of 1KW to 2KW to obtain the test results.
[0018] Based on the above, compared with the prior art, the method for detecting rare earth element content in tungsten and molybdenum materials provided by this invention uses hydrogen peroxide to dissolve the sample, eliminating the need to remove the tungsten matrix and avoiding the co-precipitation effect caused by other dissolution methods that remove the tungsten matrix. This improves the accuracy of the determination and can well meet the requirements for the determination of rare earth elements in tungsten and molybdenum alloys. Furthermore, it has a wide detection range, adapting to the detection needs of rare earth elements within the mass fraction range of 0.01% to 10%, especially within the range of 0.1% to 10%, and has good application value.
[0019] Other features and beneficial effects of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects of the invention and other beneficial effects may be realized and obtained by means of the structures and / or components pointed out in the description and claims. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. The technical features designed in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0021] In the description of this invention, it should be noted that all terms used in this invention (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains, and should not be construed as limiting the invention; it should be further understood that the terms used in this invention should be understood to have the same meaning as those in the context of this specification and in the relevant field, and should not be understood in an idealized or overly formal sense, except as expressly defined in this invention.
[0022] Example 1: Testing the lanthanum content in a tungsten-lanthanum sample. After cleaning the surface of the tungsten-lanthanum sample blank with hydrochloric acid, it was then washed with water and dried. Finally, it was pulverized into powder particles with a particle size of 300 mesh using a mortar.
[0023] The sample powder was placed in a reaction vessel, and 25 mL of hydrogen peroxide was added. After the sample powder was heated on a 250°C hot plate until dissolved and clarified, the solution was brought to a final volume to obtain the test sample solution. 0.1 g of each sample was weighed, and parallel samples were prepared.
[0024] Standard solution preparation: Weigh four 0.1g pure tungsten powder samples and dissolve them into clear solutions according to the method described for preparing the test sample solutions. Add 0, 0.5, 1, and 2 mL of lanthanum standard solution (1000ppm) to each sample, and then dilute each solution to 100 mL. Perform the test on an ICP device at the wavelength specified for the element to be tested, with a power of 1.2 kW. Obtain the intensity values corresponding to the concentration of the element at each point, and automatically fit the intensity values to the corresponding concentration values to form a curve.
[0025] The strength of the sample is tested, and the result of the lanthanum content test is obtained by converting the result on the standard curve.
[0026] The test results of the sample analysis are as follows:
[0027] Note: The theoretical values are calculated based on the elemental composition of the actual tested samples and are used as an evaluation reference. Sample 1 is a tungsten-lanthanum sample with a lanthanum content of 0.78%, Sample 2 is a tungsten-lanthanum sample with a lanthanum content of 0.92%, and Sample 3 is a tungsten-lanthanum sample with a lanthanum content of 0.0230%.
[0028] Example 2: Testing the cerium content in a tungsten-cerium sample. After cleaning the surface of the tungsten-cerium sample blank with hydrochloric acid, it was then washed with water and dried. Finally, it was pulverized into powder particles with a particle size of 300 mesh using a mortar.
[0029] The sample powder was placed in a reaction vessel, and 25 mL of hydrogen peroxide was added. After the sample powder was heated to dissolve on a 250°C hot plate, 2 mL of 50% sulfuric acid was added when cerium oxide precipitate appeared at the bottom. After complete dissolution, the volume was adjusted to obtain the test sample solution. 0.1 g of each sample was weighed, and parallel samples were prepared.
[0030] Standard solution preparation: Weigh four 0.1g pure tungsten powder samples and dissolve them into clear solutions according to the method described for preparing the test sample solution. Add 0, 0.5, 1, and 2 mL of cerium standard solution (1000ppm) to each sample, and then dilute each solution to 100mL. Select the wavelength of the element to be tested on an ICP-controlled spectroscopy device and perform the test at a power of 1.2KW. Obtain the intensity value corresponding to the concentration of the element at each point, and automatically fit the intensity value to the corresponding concentration value into a curve.
[0031] The strength of the sample is tested, and the cerium content is calculated using a standard curve.
[0032] The test results are as follows:
[0033] Note: The theoretical values are calculated based on the elemental composition of the actual tested samples and are used as an evaluation reference. Sample 4 is a tungsten-cerium sample with a cerium content of 0.88%, and Sample 5 is a tungsten-cerium sample with a cerium content of 0.94%.
[0034] Example 3 The surface of the molybdenum-lanthanum sample blank was cleaned with hydrochloric acid, then washed with water and dried, and then pulverized into powder particles with a particle size of 300 mesh using a mortar.
[0035] The sample powder was placed in a reaction vessel, and 25 mL of hydrogen peroxide was added. After the sample powder was heated on a 250°C hot plate until dissolved and clarified, the solution was brought to a final volume to obtain the test sample solution. 0.1 g of each sample was weighed, and parallel samples were prepared.
[0036] Standard solution preparation: Weigh four 0.25g samples of pure molybdenum powder and dissolve them into clear solutions according to the method described for preparing the test sample solution. Add 0, 0.5, 1, and 2 mL of lanthanum standard solution (1000ppm) to each sample, and then dilute each solution to 100mL. Perform the test on an ICP device at the wavelength specified for the element to be tested, with a power of 1.2KW. Obtain the intensity values corresponding to the concentration of the element at each point, and automatically fit the intensity values to the corresponding concentration values to form a curve.
[0037] The strength of the sample is tested, and the result of the lanthanum content test is obtained by converting the result on the standard curve.
[0038] The test results are as follows:
[0039] Note: The theoretical values are calculated based on the elemental composition of the actual tested samples and are used as an evaluation reference. Sample 6 is a molybdenum-lanthanum sample with a lanthanum content of 0.50%, and Sample 7 is a molybdenum-lanthanum sample with a lanthanum content of 0.30%.
[0040] Example 4 The surface of the molybdenum-cerium sample blank was cleaned with hydrochloric acid, then washed with water and dried, and then crushed into powder particles with a particle size of 300 mesh using a mortar.
[0041] The sample powder was placed in a reaction vessel, and 25 mL of hydrogen peroxide was added. After the sample powder was heated to dissolve on a 250°C hot plate, 2 mL of 50% sulfuric acid was added when cerium oxide precipitate appeared at the bottom. After complete dissolution, the volume was adjusted to obtain the test sample solution. 0.1 g of each sample was weighed, and parallel samples were prepared.
[0042] Standard solution preparation: Weigh four 0.25g samples of pure molybdenum powder and dissolve them into clear solutions according to the method described for preparing the test sample solution. Add 0, 0.5, 1, and 2 mL of cerium standard solution (1000ppm) to each sample, and then dilute each solution to 100mL. Perform the test on an ICP device at the wavelength of the element to be tested and a power of 1.2KW. Obtain the intensity values corresponding to the concentration of the element at each point, and automatically fit the intensity values to the corresponding concentration values to form a curve.
[0043] The strength of the sample is tested, and the result of the lanthanum content test is obtained by converting the result on the standard curve.
[0044] The test results are as follows:
[0045] Note: The theoretical values are calculated based on the elemental composition of the actual tested samples and are used as an evaluation reference. Sample 8 is a molybdenum-cerium sample with a cerium content of 0.98%, and Sample 9 is a molybdenum-cerium sample with a cerium content of 0.98%. Example 5 After cleaning the surface of the tungsten, lanthanum, and cerium sample blanks with hydrochloric acid, they were then washed with water, dried, and pulverized into powder particles with a particle size of 300 mesh using a mortar.
[0046] The sample powder was placed in a reaction vessel, and 25 mL of hydrogen peroxide was added. After the sample powder was heated to dissolve on a 250°C hot plate, 2 mL of 50% sulfuric acid was added when cerium oxide precipitate appeared at the bottom. After complete dissolution, the volume was adjusted to obtain the test sample solution. 0.1 g of each sample was weighed, and parallel samples were prepared.
[0047] Standard solution preparation: Weigh four 0.1g pure tungsten powder samples and dissolve them into clear solutions according to the method described for preparing the test sample solutions. Add 0, 0.5, 1, and 2 mL of lanthanum standard solution (1000ppm) to each sample, and then dilute each solution to 100 mL. Perform the test on an ICP device at the wavelength specified for the element to be tested, with a power of 1.2 kW. Obtain the intensity values corresponding to the concentration of the element at each point, and automatically fit the intensity values to the corresponding concentration values to form a curve.
[0048] Simultaneously, four 0.1g pure tungsten powder samples were weighed and dissolved into clear solutions according to the preparation method of the test sample solution. 0, 0.5, 1, and 2 mL of cerium standard solution (1000ppm) were added to each sample, and then each solution was brought to a final volume of 100 mL. The wavelength of the element to be tested was selected on an ICP-controlled spectroscopy device, and the test was performed at a power of 1.2 kW. The intensity values corresponding to the element's concentration at each point were obtained, and the intensity values were automatically fitted to the corresponding concentration values to form a curve.
[0049] The strength of the sample is tested, and the results of the lanthanum and cerium content are obtained by converting the values on the standard curve.
[0050] The test results are as follows:
[0051] Note: The theoretical values are calculated based on the elemental composition of the actual tested samples and are used as an evaluation reference. Sample 10 is a tungsten-lanthanum-cerium sample with a lanthanum content of 1.00% and a cerium content of 0.50%, and Sample 11 is a tungsten-lanthanum-cerium sample with a lanthanum content of 1.00% and a cerium content of 0.50%.
[0052] Comparative Example 1 The same sample as in Example 3 was tested using existing spectroscopic methods: The specific sample processing procedure is as follows: 20 mL of hydrogen peroxide and 1 mL of hydrochloric acid are added to 0.100 g of molybdenum-lanthanum sample, and the sample is placed at 60 °C to completely decompose the sample and then cooled. The pH of the solution is then adjusted with ammonia, heated at 60 °C for 5 min, and then cooled. The resulting solution is filtered and the precipitate is washed with ammonia and deionized water. The precipitate was completely dissolved in 100 mL volumetric flask with 12% hydrochloric acid at 70 °C. 10 mL of hydrochloric acid and 1.0 mL of cesium internal standard solution were added, mixed well, and diluted to volume to obtain the sample solution to be tested.
[0053] Lanthanum standard solutions of different concentrations were prepared, and the signal intensities of lanthanum and cesium in the standard solutions of different concentrations were measured using inductively coupled plasma mass spectrometry. A standard curve was plotted showing the relationship between the signal intensity ratio of lanthanum and cesium and their concentrations. The sample solution was measured using inductively coupled plasma mass spectrometry to obtain the signal intensity ratio of lanthanum to internal standard. The concentration of lanthanum was obtained by substituting the signal intensity into the standard curve of lanthanum, and the mass fraction of the impurity element was calculated.
[0054] The test results are as follows:
[0055] Based on the measured values and theoretical values, the measured values of samples 6 and 7 using the existing spectroscopic method differed significantly from the theoretical values, indicating that the existing spectroscopic method is not suitable for the detection of the content of constant rare earth elements.
[0056] Comparative Example 2 The same tungsten-lanthanum sample from Example 1 was analyzed using a colorimetric method. Step 1: In a triethanolamine alkaline medium, lanthanum is precipitated using magnesium as a carrier, and then the lanthanum hydroxide precipitate is dissolved using acetic acid ascorbic acid.
[0057] Step 2: Adjust the pH of the solution to a weakly acidic level of 2-3. Then add the complexing colorimetric reagent azoarsine III to form a colored complex with a complexation ratio of 1:1. Measure the complex colorimetrically at 650 nm. (Trace amounts of iron, aluminum, and copper can be masked by adding appropriate amounts of ascorbic acid, sodium dihydrogen phosphate, and sodium sulfosalicylate.)
[0058] The test results are as follows:
[0059] Comparative Example 3 The same tungsten-cerium sample was analyzed using a colorimetric method in Experiment 2.
[0060] The test results are as follows:
[0061] Comparative Example 4 The same molybdenum-lanthanum sample was analyzed using a colorimetric method.
[0062] The test results are as follows:
[0063] Comparative Example 5 Four identical molybdenum-cerium samples were analyzed using a colorimetric method.
[0064] The test results are as follows:
[0065] Comparative Example 6 The same tungsten, lanthanum, and cerium samples were analyzed using a colorimetric method.
[0066] The test results are as follows:
[0067] It should be noted that the specific parameters or some commonly used reagents in the above embodiments are specific or preferred embodiments under the concept of the present invention, and not limitations thereof; those skilled in the art can make adaptive adjustments within the concept and protection scope of the present invention.
[0068] In addition, unless otherwise specified, the raw materials used may be commercially available products in the field or prepared by conventional methods in the field.
[0069] The standard deviation and relative deviation of the test results of Comparative Examples 1-5 and Comparative Examples 2-6 were analyzed, and the results are shown in Table 1.
[0070] Table 1. Analysis of Test Results
[0071] Note: The average relative deviation is the relative deviation between the average measured value and the theoretical value.
[0072] As shown in Table 1, the standard deviations of Examples 1-5 are all below 0.4%, and the average relative deviations are all below 8%, with most cases below 3%. This fully demonstrates that the method for detecting rare earth element content in tungsten and molybdenum materials provided by this invention not only has good stability but also high accuracy. However, the results of Comparative Examples 2-6 show that the colorimetric method, when the rare earth element content is non-trace (>0.1%), has an average relative deviation of over 15%, often reaching 20%, and even exceeding 30% when cerium is present in the rare earth element content. This indicates that the colorimetric method is not suitable for detecting rare earth elements in the non-trace range.
[0073] Furthermore, samples with high rare earth element content (≥5%) were tested.
[0074] Example 6 Example 6 uses the same detection method as Example 1, the difference being that it uses a sample with a high content of tungsten and lanthanum.
[0075] The test results are as follows:
[0076] Note: The theoretical values are calculated based on the elemental composition of the actual tested samples and are used as an evaluation reference. Sample 12 is a tungsten-lanthanum sample with a lanthanum content of 5.00%, and Sample 13 is a tungsten-lanthanum sample with a lanthanum content of 10.00%.
[0077] Example 7 Example 7 uses the same detection method as Example 2, the difference being that it uses a sample with a high content of tungsten and cerium.
[0078]
[0079] Note: The theoretical values are calculated based on the elemental composition of the actual tested samples and are used as an evaluation reference. Sample 14 is a tungsten-cerium sample with a cerium content of 5.00%, and Sample 15 is a tungsten-cerium sample with a cerium content of 10.00%.
[0080] The detection of high-rare-earth element samples using colorimetric methods and existing spectroscopic methods suffers from severe distortion, failing to yield results close to theoretical values. However, the rare-earth element content detection method in tungsten and molybdenum materials provided by this invention, as shown in Examples 6 and 7, although the standard deviation increases due to the larger overall data size, the average relative deviation remains below 3%. This fully demonstrates that the rare-earth element content detection method in tungsten and molybdenum materials provided by this invention can still obtain relatively stable and accurate test data in the detection of high-rare-earth element samples, illustrating the superiority of the rare-earth element content detection method provided by this invention.
[0081] In summary, compared with existing technologies, the method for detecting rare earth element content in tungsten and molybdenum materials provided by this invention uses hydrogen peroxide to dissolve the sample, eliminating the need to remove the tungsten matrix and avoiding the co-precipitation effect caused by other dissolution methods that remove the tungsten matrix. This improves the accuracy of the determination and can well meet the requirements for the determination of rare earth elements in tungsten and molybdenum alloys. Furthermore, it has a wide detection range, adapting to the detection needs of rare earth elements with a mass fraction range of 0.01% to 10%, and has good application value.
[0082] Furthermore, those skilled in the art should understand that although many problems exist in the prior art, each embodiment or technical solution of the present invention can be improved in only one or a few aspects, without necessarily solving all the technical problems listed in the prior art or the background art simultaneously. Those skilled in the art should understand that any content not mentioned in a claim should not be construed as a limitation on that claim.
[0083] Although this document frequently uses terms such as rare-earth-doped alloys and dissolving solutions, the possibility of using other terms is not excluded. These terms are used merely for the convenience of describing and explaining the essence of the invention; interpreting them as any additional limitation would contradict the spirit of the invention. The terms "first," "second," etc. (if present) in the description and claims of the embodiments of the invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for detecting the rare earth element content in tungsten materials, characterized in that, The steps are as follows: The rare earth-doped alloy sample to be tested was pre-treated by crushing to obtain sample powder. The sample powder is dissolved in a dissolving solution to obtain the sample solution to be tested; A standard curve for tungsten alloys was established, and the sample solution was detected using inductively coupled plasma mass spectrometry. The crushing pretreatment process is as follows: The sample to be tested is cleaned with a cleaning solution, rinsed with water, dried, and then pulverized into powder particles to obtain the sample powder; the particle size of the powder particles is at least 300 mesh. The dissolution process is as follows: Place 0.1g of the sample powder in a reaction vessel, add 25mL of hydrogen peroxide, and after the sample powder is heated to 250°C and dissolved and clarified, bring the volume to a final volume to obtain the sample solution to be tested; when the rare earth doped alloy sample is doped with cerium, add sulfuric acid after dissolving in hydrogen peroxide until cerium oxide precipitate appears at the bottom; The rare earth element doping content in the rare earth doped alloy sample is 0.01% to 10% by mass fraction.
2. The method for detecting rare earth element content in tungsten materials according to claim 1, characterized in that: The rare earth elements in the rare earth doped alloy sample are any one or a combination of lanthanum, cerium, praseodymium, samarium, gadolinium, neodymium, and yttrium.
3. The method for detecting rare earth element content in tungsten materials according to claim 1, characterized in that: The process for establishing the standard curve is as follows: Five 0.1g pure tungsten samples were weighed, dissolved in hydrogen peroxide, and then 0, 0.5, 1, 2, and 4 mL of 1000ppm target rare earth element standard solution were added respectively. The volume was then adjusted to 100mL. The solutions of each concentration were then placed in an inductively coupled plasma mass spectrometer. The instrument displayed the intensity values of the target rare earth element at each concentration point and fitted the intensity values with the corresponding concentration values to form a curve.
4. The method for detecting rare earth element content in tungsten materials according to claim 1, characterized in that: The inductively coupled plasma mass spectrometry detection method is as follows: Select the wavelength of the element to be measured; set the concentration of the standard curve of the element to be measured; conduct the test at a test power of 1KW to 2KW to obtain the test results.
Citation Information
Patent Citations
Measurement method of trace-amount rare earth impurity element in W-La alloy
CN104515796A